Reducing Exacerbations in the Inner City: Lessons from the Inner City Asthma Consortium (ICAC) - Gergen, Peter J. (J Allergy Clin Immunol Pract, 2015)
Asthma exacerbations are important components of asthma morbidity. The Inner City Asthma Consortium was established in the early 1990’s to identify risk factors for and to evaluate treatments to reduce asthma symptoms and exacerbations. Early studies identified atopy and inadequate treatment as important drivers of asthma morbidity. Later studies demonstrated that good adherence to guidelines based asthma care could virtually eliminate symptoms and reduce but not eliminate exacerbations. Looking at exacerbations by season, risk factors were found to vary across the different seasons. Of the seven factors identified, allergic status and pulmonary functions were found to be important for exacerbations in all seasons but allergy had its strongest effect in the fall season. Therefore, additional therapy directed at reducing the role of allergy was evaluated and found to significantly reduce exacerbations even in participants with good symptom control when receiving guidelines based therapy. Despite this aggressive therapy, exacerbations remain albeit at a lower level and with less seasonal variation. An ongoing trial evaluating two different approaches to pre-seasonal interventions directed at individuals at high risk for exacerbations during the subsequent season may offer an effective alternative to minimize exacerbations and to limit the amount of therapy necessary.